Language Switching and Language Representation in Spanish–English Bilinguals: An fMRI Study - Hernandez, Arturo E.; Dapretto, Mirella; Mazziotta, John; Bookheimer, Susan (NeuroImage (Orlando, Fla.), 2001)
The current experiment was designed to investigate the nature of cognitive control in within- and between-language switching in bilingual participants. To examine the neural substrate of language switching we used functional magnetic resonance imaging (fMRI) as subjects named pictures in one language only or switched between languages. Participants were also asked to name (only in English) a separate set of pictures as either the actions or the objects depicted or to switch between these two types of responses on each subsequent picture. Picture naming compared to rest revealed activation in the dorsolateral prefrontal cortex, which extended down into Broca's area in the left hemisphere. There were no differences in the activation pattern for each language. English and Spanish both activated overlapping areas of the brain. Similarly, there was no difference in activation for naming actions or objects in English. However, there was increased intensity of activation in the dorsolateral prefrontal cortex for switching between languages relative to no-switching, an effect which was not observed for naming of actions or objects in English. We suggest that the dorsolateral prefrontal cortex serves to attenuate interference that results from having to actively enhance and suppress two languages in alternation. These results are consistent with the view that switching between languages involves increased general executive processing. Finally, our results are consistent with the view that different languages are represented in overlapping areas of the brain in early bilinguals.